Plan Prototype Microcontroller based 30 Meter Running Speed Test Equipment - Bangun Setia Hasibuan; Suharjo Suharjo; Afri Tantri; Muhammad Reza Destya (UNIB Press, 2023)
This research aims to produce a 30 meter running speed equipment product athlete North Sumatra which is microcontroller based. It is hoped that this research will be able to overcome the difficulties faced by testers which have so far been carried out manually so that they are effective and effective objectivity The results of this test still cannot be categorized as accurate. This research uses an approach of research and development with the Borg and Gall model which is divided into three stages. The research stages are; (1) Pre-development stage, which one At this stage, a needs analysis is carried out through survey level of tool requirements for users, preparation instrument and consultation to experts. (2) Development stage develop products running speed 30 meters starting from developing initial product manuscripts (manual books), designing digital tools, trials small group, stage I improvement, trials large group, phase II improvement, mass production. (3) Evaluation stage implementation of product results and dissemination product. The results of the analysis from the trial I obtained an average value implementation of Microcontroller-Based 30 Meter Running Speed ​​Test Equipment based on data obtained for the answer